1998
DOI: 10.1021/bi9800202
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Ubiquinone Reduction Site of Mitochondrial Complex I Using Bulky Synthetic Ubiquinones

Abstract: A wide variety of alkyl derivatives of Q2 (6-geranyl-2, 3-dimethoxy-5-methyl-1,4-benzoquinone) and DB (6-n-decyl-2, 3-dimethoxy-5-methyl-1,4-benzoquinone), in which methoxy groups of the 2- and/or 3-positions of the quinone ring were replaced by other bulky alkoxy groups from ethoxy to butoxy, were prepared by novel synthetic procedures. Electron-accepting activities of the bulky quinones were investigated with bovine heart mitochondrial complex I and its counterpart of Paracoccus denitrificans(NDH-1) to eluci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 39 publications
6
40
1
Order By: Relevance
“…The idea of a fairly large ubiquinone binding domain also fits well with recently published data showing that this pocket is sufficiently spacious to accommodate rather bulky exogenous ubiquinones (52).…”
Section: Discussionsupporting
confidence: 87%
“…The idea of a fairly large ubiquinone binding domain also fits well with recently published data showing that this pocket is sufficiently spacious to accommodate rather bulky exogenous ubiquinones (52).…”
Section: Discussionsupporting
confidence: 87%
“…This fits well with the proposed proximity of this subunit with NuoB, NuoD, and NuoH (42). Because the binding of the various inhibitors is affected by the presence of other inhibitors, it was concluded that these binding sites partially overlap (43). Here, we have shown that the binding of [ 3 H]azido-Q is not influenced by addition of inhibitors, indicating that the inhibitor binding site(s) may not be identical to the quinone binding site(s).…”
Section: Effects Of Cofactors On the Labeling Of Nuom By [ 3 H]azido-q-supporting
confidence: 81%
“…Succinate-quinone reductase activities were measured as described previously (21). DMQ 2 and 3-hydroxy-UQ 2 were synthesized as described previously (22). All the assays were performed at 20°C.…”
Section: Methodsmentioning
confidence: 99%